SÄRAT YUSUF (SUNTINGAN TEKS DAN TERJEMAHAN) - , NADYA SALIMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
SÄrat Yusuf is kept as one of priceless collection in the library of Widyapustaka Pakualaman with a code st. 83/0030/PP/73. The works of SÄrat Yusuf was written in the form of a Macapat or a poem written in Pegon script using Javanese language. The paper presents the result of the research which covers general description of the works containing information related to the manuscript of SÄrat Yusuf, the edited text with text correction method, completed with word to word translation and conclusion in which some recommendation are included. The writer defines some special spelling by himself which are actually different to that of Javanese dictionary. Therefore, the writing of those words are conformed to the dictionary and is completed with some notes. The case is found in the writing of dispelling nasal (n, m and ng), changing nasal (ny) and the switch of word dhumatÄng toward dathÄng in which the written character (d) is edited to be (dh). The manuscript of SÄrat Yusuf part I to part IV narrates the lifeline of Prophet Yusuf opened with his acquisition of sign through his dream telling that someday Yusuf would be a leader which would make him being hated by his siblings and plunged into a well. Meantime, inside of the well a man named Ki Hud, who is not mentioned in the Quran, had been waiting. Ki Hud had asked to the God to see Yusuf. After the long time waiting, Ki Hud finally met Yusuf and then he told Yusuf that someday Yusuf would become the king of Egypt. However, the expected joy had flight away when Ki Hud passed away. At last, Yusuf had been founded by an Egyptian merchant and taken as a servant by the merchant.